Effect of dry thermal oxidation on the microstructure and magnetic properties of SmCo5 permanent magnet. (September 2021) - Mittireddi, Ravi Teja; Singh, Ranjan Kumar; Panda, Emila
Graphical abstract: Highlights: Oxidation of SmCo5 by varying a range of process parameters is carried out. Sm2 O3, the thermodynamically most stable phase is found only in minor quantities. Cobalt segregation led the formation of Co3 O4 as the primary oxide phase. At T > 973 K cobalt incorporation in Sm2 O3 lattice led the formation of SmCoO3 . The developed oxide microstructure led significant change in magnetic properties. Abstract: Understanding the microstructural changes in SmCo5 because of oxidation and thereby altered magnetic properties will help in designing permanent magnets which could retain their magnetic properties in adverse environments. In this regard, the present study investigates the thermal oxidation of SmCo5 magnets by varying temperature (373−973 K), time (1, 5 h) and pressure (1.013 × 10 5 and 4.6 × 10 −5 Pa). Increased Co segregation towards the surface is found and this impacts the overall oxidation mechanism to a large extent. In the end, the developed oxide-film microstructure and microstructural changes in the bulk are correlated with the induced changes in the magnetic properties.